Completion surgery of residual disease after primary inadequate surgery of retroperitoneal sarcomas can salvage a selected subgroup of patients—A propensity score analysis. Issue 3 (16th December 2018) - Nizri, Eran; Fiore, Marco; Colombo, Chiara; Radaelli, Stefano; Callegaro, Dario; Sanfilippo, Roberta; Sangalli, Claudia; Collini, Paola; Morosi, Carlo; Stacchiotti, Silvia; Casali, Paolo G.; Gronchi, Alessandro
Abstract : Background: Patients with retroperitoneal sarcoma (RPSs) who undergo primary inadequate surgery before referral to specialized sarcoma centers may be considered for completion surgery (CS). We wanted to compare the outcome of these patients to those who underwent primary adequate surgery (PAS) at a single referral institution. Methods: We identified 34 patients who were referred for CS after primary inadequate surgery. Using a propensity score based on validated RPS outcome risk factors, we managed to match 28 patients to patients with PAS. Results: Median time lag between the first and second operation in CS patients was 5 months (2‐15). Surgical extent was similar among groups (median number of organs resected = 3; P = 0.08), and macroscopically complete excision was achieved in all patients. The rate of severe complications did not differ between the groups (1 of 28 vs 3 of 28, respectively; P = 0.35) and no perioperative mortality was documented. Median follow‐up was 43.5 months. Patients in the CS group had similar local recurrence‐free survival (mean, 92.1 ± 9.7 vs 99.8 ± 12.4; P = 0.85) and relapse‐free survival (mean, 88.7 ± 9.8 vs 80.9 ± 12.3; P = 0.3) to those with PAS. Conclusions: CS has short‐ and long‐term outcomes comparable to PAS. While primary surgery should always be carried out at a referral institution, some of the patients who undergo an initial incomplete resection at a non specialist center can still be offered a salvage procedure at a referral institution with comparable results.